Związki polityki i ekonomii w badaniu stosunków międzynarodowych - Matera, Paulina (Przegląd Strategiczny, 2012)
The objective of this article is to present the development of the International Political Economy (IPE) as the sub-discipline of the international relations. It deals with the influence of political decisions on the economy, and the economic situation on the political activities of the states. The genesis of the IPE can be traced in the 1970s. when the major changes in the world economy occurred. The greater attention was paid to the impact of those events on the international relations and the policy of particular states. The pioneer books were published then: theoretical ones and the works which presented the international relation from a new perspective. The article includes also the basic definitions, the scope of the research as well as the methodology applied in the IPE. The theories (based on mercantilism, liberalism and structuralism) and the new approaches: ecological, feminist critique etc. are also presented. In the last part of the text the concepts of the role of the economic factor in foreign and domestic policy of the nation states are analyzed.